2019
DOI: 10.1074/jbc.ra119.009671
|View full text |Cite
|
Sign up to set email alerts
|

A general protein O-glycosylation machinery conserved in Burkholderia species improves bacterial fitness and elicits glycan immunogenicity in humans

Abstract: The Burkholderia genus encompasses many Gram-negative bacteria living in the rhizosphere. Some Burkholderia species can cause life-threatening human infections, highlighting the need for clinical interventions targeting specific Burkholderia proteins. Burkholderia cenocepacia O-linked protein glycosylation has been reported, but the chemical structure of the O-glycan and the machinery required for its biosynthesis are unknown and could reveal potential therapeutic targets. Here, using bioinformatics approaches… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
70
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
2

Relationship

4
3

Authors

Journals

citations
Cited by 29 publications
(78 citation statements)
references
References 65 publications
4
70
1
Order By: Relevance
“…Although these results support the breakdown of BCAL1086 as a consequence of the loss of glycosylation, an alternative explanation is that the changes in degradation arise from alterations in protease levels or activities in the ∆pglL mutant. Previously, we reported that ∆pglL results in enhanced casein proteolytic activity (65). However, our global proteome analysis shows only modest changes in protease levels.…”
Section: The Observation That Biofilm Formation Is Reduced In Pgll Mcontrasting
confidence: 52%
See 3 more Smart Citations
“…Although these results support the breakdown of BCAL1086 as a consequence of the loss of glycosylation, an alternative explanation is that the changes in degradation arise from alterations in protease levels or activities in the ∆pglL mutant. Previously, we reported that ∆pglL results in enhanced casein proteolytic activity (65). However, our global proteome analysis shows only modest changes in protease levels.…”
Section: The Observation That Biofilm Formation Is Reduced In Pgll Mcontrasting
confidence: 52%
“…We previously demonstrated that loss of glycosylation causes defects in motility (56), reduction of virulence in plant and insect infection models (56,65), and defects in carbon utilisation (65). To better understand the role of glycosylation in B. cenocepacia we assessed the effect of loss of glycosylation on the proteome.…”
Section: Loss Of Glycosylation In B Cenocepacia Leads To Global Protmentioning
confidence: 99%
See 2 more Smart Citations
“…While glycosylation in bacteria was first identified in the 1970s [20], it is only within the last two decades that it has become clear that this class of modifications is ubiquitous across bacterial genera [16, 18, 21]. Unlike Eukaryotic systems, which utilise a relatively small set of monosaccharides, bacterial glycoproteins are decorated with a diverse range of monosaccharides [22] leading to a staggering array of glycan structures [2332]. This glycan diversity represents a significant challenge to the field as it makes the identification of novel bacterial glycoproteins a non-trivial analytical undertaking.…”
Section: Introductionmentioning
confidence: 99%